A7.3 The mucosal anti-citrullinated protein antibody response in pre-clinical rheumatoid arthritis. (13th February 2015) - Van der Horst, A; Choi, YK; van Schaardenburg, DJ; Gerlag, DM; Hamann, D; Tak, PP; Thurlings, RM
Abstract : Background: Recent data suggest rheumatoid arthritis (RA) may originate from an autoimmune response in inflamed mucosa. When aiming to prevent arthritis it is critical to understand the source and regulation of autoantibody production in preclinical RA. Objective: To determine whether ACPA are produced at mucosal sites in ACPA positive individuals at risk for RA and to compare the ACPA isotype and fine specificity in mucosal fluids to peripheral blood. Materials: Saliva, sputum, faeces and peripheral blood were collected during an early morning visit from 15 individuals with anti-cyclic cit protein (anti-CCP2) antibody positive arthralgia who are part of a cohort that is being prospectively followed for the possible development of arthritis. Sputum was induced by inhalation of sodium chloride aerosols 4.5%. Mucus plugs were selected from sputum for extraction of supernatants. IgG and IgA ACPA were measured in mucosal fluids and blood using two cit fibrinogen peptides, one enolase peptide and one vimentin peptide and their arginine peptides as control. Results: Eleven of 15 individuals tested positive for anti-CCP2 and ACPA in their blood at the day of mucosal fluid collection. Four patients tested positive for anti-CCP2 but negative for the tested ACPA. IgG Anti-cit fibrinogen, enolase and vimentin antibodies were detected in respectively 11, 4 and 3 individuals. In 3 individuals IgA anti-cit fibrinogen and anti-cit vimentin antibodies were present. The saliva of 5 patients contained ACPA with IgA anti-cit enolase and anti-cit fibrinogen in 4 patients and IgG anti-cit enolase and anti-cit fibrinogen in 2 patients. The sputum of one patient contained IgA anti-cit-fibrinogen. Other samples tested negative for ACPA. There were no differences in ACPA number or type in blood between patients with or without mucosal ACPA. All 5 patients with ACPA in saliva had the same antibodies in blood, in 4 of 5 individuals only of IgG class. In 2 of 5 patients ACPA were detected in blood that were not detected in saliva. Conclusion: Collection of saliva, sputum and faeces allows for the detection of ACPA in the mucosal secretions of a proportion of anti-CCP positive individuals at risk for RA. In these patients, ACPA in blood are predominantly of the IgG class and in some patients directed against more peptides compared to ACPA in secretions. Future analyses should focus on further defining the precise source and regulation of mucosal and systemic ACPA.